1976
DOI: 10.1021/bi00664a020
|View full text |Cite
|
Sign up to set email alerts
|

Conformational properties of the complexes formed by proteins and sodium dodecyl sulfate

Abstract: Circular dichroism spectra have been obtained for albumin, alpha-chymotrypsinogen, collagen, concanavalin A, elastase, hemoglobin, histone f2b, alpha-lactalbumin, lactate dehydrogenase, beta-lactoglobulin, lysozyme, myoglobin, papain, ribonuclease A, and thermolysin in the presence of sodium dodecyl sulfate and dithiothreitol. While all spectra have the shape anticipated for a mixture of random coil and alpha helix, the intensities differ markedly ([theta]222 ranges from --1400 to --15 000 deg cm2/dmol). The v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
95
0

Year Published

1977
1977
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 234 publications
(106 citation statements)
references
References 83 publications
11
95
0
Order By: Relevance
“…Analysis of these curves by the method of Provencher and Glockner (1981) showed that the a-helix and fl-sheet content of the two contrazymes were increased slightly in the presence of sodium dodecyl sulfate. Similar changes have been observed in several other globular proteins (Mattice et al 1976). There is, however, no marked difference between contrapsin and a-l-antitrypsin, indicating that the main chain structure of the two murine proteins are very similar in the presence of sodium dodecyl sulfate.…”
Section: Resultssupporting
confidence: 85%
“…Analysis of these curves by the method of Provencher and Glockner (1981) showed that the a-helix and fl-sheet content of the two contrazymes were increased slightly in the presence of sodium dodecyl sulfate. Similar changes have been observed in several other globular proteins (Mattice et al 1976). There is, however, no marked difference between contrapsin and a-l-antitrypsin, indicating that the main chain structure of the two murine proteins are very similar in the presence of sodium dodecyl sulfate.…”
Section: Resultssupporting
confidence: 85%
“…Residual structure (at room temperature) in SDS denatured states of proteins is not uncommon. Serum albumin [19] and a number of other proteins show different degrees of secondary structure, when exposed to high concentrations of ionic surfactants [11,16,[52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…This anionic compound, which is generally considered a potent denaturant [4], was investigated in many early works on bovine serum albumin (BSA) [5][6][7][8][9][10] and a number of other proteins [11][12][13][14][15][16][17]. This led to several general conclusions regarding the modes of interaction of SDS and proteins (for reviews see [18][19][20]).…”
mentioning
confidence: 99%
“…TFE appears to stabilize the secondary structure for which a peptide has a propensity to form (Zhong & Johnson, 1992). SDS has also been shown to induce secondary structure formation in some peptides (Bansal et al, 1990;Zhong & Johnson, 1992); in the case of proteins, the situation is much more complex (Mattice et al, 1976). In aqueous 30% TFE and 50 mM aqueous SDS, the far-UV CD spectra in both solutions revealed minima at 220 nm and 208 nm, which are characteristic of peptides or proteins possessing a high percentage of helical content (Fig.…”
Section: Urea-gradien T Gel Electrophoresismentioning
confidence: 97%